Diversity, species composition and distribution of odonates (odonata) in Johor state, peninsular Malaysia - Abdul Aziz, Muhamad Amirul Ashraf (2018)
Johor is undergoing rapid socioeconomic development; some forms of prioritization of conservation area are needed as the best resemblance of original biodiversity. Through effective management, it would assist the state for a better conservation practice. The purpose of this research is to provide a baseline data of odonates in Johor to facilitate prioritization of conservation areas as well as in planning, managing and sustainable usage of biodiversity. The objectives of this research are to determine the diversity and species composition of odonates in selected sites in Johor, to map distribution pattern based on faunistic and ecological aspects and to identify identify prioritize conservation areas and potential sites for odonate tourism using priority grid analysis based on specific criteria. Samplings were carried out from November 2016 to October 2017 in nine selected sites in Johor. Adult odonates were collected using aerial net in each of the 21 stations located at equidistant of 50 m along a one km transect for a total of 648 man-hours. The species distribution map of odonate was determined using both direct and indirect approaches in visualizing the distribution patterns. Total of 2,222 individuals of 84 species from 13 families and 58 genera were recorded. From all the nine sites, Libellulidae was the most well-represented family in terms of species richness (44%) and abundance (59%). Shannon Diversity Index (H’), and Species Evenness Index (E’) were highest in Taman Negara Johor Endau-Rompin (H’= 3.16; E’= 0.73) and lowest in Hutan Lipur Soga Perdana (H’= 2.44; E’= 0.50). The site with highest priority was Hutan Lipur Sungai Bantang with a score value of 62 while the lowest priority was recorded in Hutan Lipur Gunung Pulai with a score value of 23. Similarly, site with the highest potential towards odonate tourism was Hutan Lipur Sungai Bantang with score value of 99 and Hutan Lipur Gunung Pulai being the lowest with score value of 55.This study indicated the usefulness of species distribution mapping as a tool to prioritize conservation areas. In addition, this study reveals the potential of odonates as product for entomotourism in Johor.